2012
DOI: 10.1016/j.anbehav.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Usage and comprehension of manual gestures in wild chimpanzees

Abstract: An important element in understanding the evolutionary origin of human language is to explore homologous traits in cognition and communication between primates and humans (Burling, 1993, Hewes, 1973. One proposed modality of language evolution is that of gestural communication, defined as communicative movements of hands without using or touching objects (de Waal, 2003). While homologies between primate calls and language have been relatively well explored, we still have a limited understanding of how cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 131 publications
(296 reference statements)
0
97
0
Order By: Relevance
“…However, perceived morphological variation is often considered to lack communicative function, and subsequently, gesture variants are lumped together (Hobaiter & Byrne, 2011; but see Roberts et al, 2012). The underlying assumptions are that a human observer can identify and classify meaningful units (in a similar manner to the animals themselves) and also that similar morphological properties reflect similarities in function.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, perceived morphological variation is often considered to lack communicative function, and subsequently, gesture variants are lumped together (Hobaiter & Byrne, 2011; but see Roberts et al, 2012). The underlying assumptions are that a human observer can identify and classify meaningful units (in a similar manner to the animals themselves) and also that similar morphological properties reflect similarities in function.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, not all studies investigated whether the observed signals are intentional, as determined from the signaller directing gestures to recipients in flexible, goal-directed ways (see e.g. Roberts et al, 2012). However, it is important to determine whether the observed behaviours are voluntary because the distinction between simple behavioural actions, which may be used by others to infer intentions and meaningful gestural communication, lies in determining whether the action is used intentionally (Bates, Benigni, Bretherton, Camaioni, & Volterra, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations